Religious congregations, education and school in Italy in the nineteenth century - Sani, Roberto (Historia y Memoria de la Educación, 2016)
This article traces the origins and development of about 140 new religious male and female congregations, established in Italy during the Nineteenth century. Starting from the Restoration period, the article frames the actions and choices of the new religious congregations with reference to the new scenarios produced by the revolutionary experience and by the changes introduced in ecclesiastical legislation and in the relations between State and Church during the Napoleonic era. At the same time, it deals with the unusual challenges the Church had to face due to both the secularization of mentality and customs and the increased educational needs and welfare of the post-revolutionary period. The author analyses some characteristics of these new religious institutions, most of which chose as privileged —and sometimes exclusive— activity of their apostolate the assistance (of poor and sick people, and of abandoned children and youth), the catechesis and animation of religious life in the parishes and, above all, the education of youth of both sexes and of different social classes. Firstly, the author describes the aspect related to the general adoption of the structure of religious congregations, which provides unequivocal evidence of the prevalence, also on the female side, of the traditional monastic model, of a vocation to religious life understood essentially as an active life devoted to charity, a synthesis between action and prayer, a commitment in the world through the assistance of others. The author’s reconstruction also shows how the idea of charity promoted by the new religious congregations was understood not simply as a commitment to provide assistance, but also, and above all, as an educational responsibility. Indeed, the new religious congregations considered education, school and parish catechesis as the most effective tools for Christians’ education. At the same time, school and education were also seen as the most direct and useful tool for relieving poverty and overcoming the marginalisation of the poorer classes and as the most effective tool for facilitating the successful integration of young working class men and women into society.